Small Group Discussion Strategies Reviewed to Improve Student Learning Outcomes in Civics Learning at MI Sultan Agung - Rustyaningsih, Wahyu (DEEP LEARNING: Journal of Educational Research, 2025)
This study aims to examine the effectiveness of small group learning strategies in improving student learning outcomes in Civics Education at MI Sultan Agung. Civics, as a subject, plays a crucial role in shaping students' character, sense of responsibility, and awareness of democratic values. However, traditional teaching methods often result in passive student participation and low academic performance. To address this issue, this research implemented a classroom action research (CAR) approach consisting of two cycles, each comprising planning, action, observation, and reflection. The subjects of the study were fifth-grade students at MI Sultan Agung, totaling 28 participants. Data collection techniques included observation, tests, and documentation. The findings indicate a significant improvement in student learning outcomes after applying small group learning strategies. In the first cycle, the average student learning outcome reached 68.21, with 60.71% of students achieving the minimum mastery criterion (MMC). In the second cycle, the average score increased to 82.14, with 89.29% of students achieving the MMC. Furthermore, student engagement and participation in the learning process showed marked improvement, indicating that small group strategies promote collaboration, active learning, and critical thinking. These results support the conclusion that small group learning is an effective pedagogical approach for enhancing both cognitive and affective learning outcomes in Civics Education. This study contributes to the growing body of research advocating for student-centered learning environments and highlights the importance of interactive teaching methods in primary education. The implementation of small group learning is recommended as a sustainable strategy to improve educational quality, particularly in the context of civic education, where active student involvement is essential. Future research may explore the long-term impact of this strategy and its application across different subjects and educational settings.